2022
DOI: 10.1186/s12885-022-09443-1
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal muscle loss during neoadjuvant chemotherapy predicts poor prognosis in patients with breast cancer

Abstract: Background The skeletal muscle index (SMI), which is calculated as the ratio of skeletal muscle area at the third lumbar vertebral level divided by height squared, has been considered a prognostic factor in patients with breast cancer. However, the prognostic impact of changes in SMI during treatment remains unclear. This study aimed to evaluate the influence of SMI changes in patients with breast cancer undergoing neoadjuvant chemotherapy (NAC). Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 57 publications
2
6
1
Order By: Relevance
“…Despite overall significant muscle loss, this outcome is not inevitable. This is illustrated by waterfall plots of muscle change in patients with different cancers and treatments (breast, head and neck, esophageal) shown by several authors [14,18,26]; also see Fig. 2.…”
Section: Endemic Muscle Loss During Systemic Cancer Therapymentioning
confidence: 89%
See 1 more Smart Citation
“…Despite overall significant muscle loss, this outcome is not inevitable. This is illustrated by waterfall plots of muscle change in patients with different cancers and treatments (breast, head and neck, esophageal) shown by several authors [14,18,26]; also see Fig. 2.…”
Section: Endemic Muscle Loss During Systemic Cancer Therapymentioning
confidence: 89%
“…This serial biopsy approach allowed the investigators to record changes in mitochondrial biogenesis, mitochondrial dynamics and mitophagy [49 ▪▪ ] as well as fatty infiltration [50], specific to a treatment plan that includes anthracycline, cyclophosphamide and taxane. Although muscle mass loss was undetectable by CT when patients received this regimen [12,13 ▪ ,14] (see above), microscopic and biochemical tests reveal important changes.…”
Section: Molecular Pathways Of Systemic Treatment-related Muscle Lossmentioning
confidence: 97%
“…No previous breast cancer studies in South Korea have specified how much muscle mass was lost during neoadjuvant chemotherapy, but compared to studies performed in other countries, we observed a slightly higher SMI at baseline and a slightly lower SMI after chemotherapy, despite the fact that no metastatic cancer was present in our patients. As decreased SMI after neoadjuvant chemotherapy poses a threat to disease-free survival [25], decreased SMI should be given attention when determining the direction of clinical treatment and evaluating treatment effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological data show that skeletal muscle wasting is seen in most cancers [ 19 , 20 ]. Skeletal muscles are more affected than other organs during CC [ 21 , 22 ], however our understanding of why skeletal muscle is more affected by CC is incomplete.…”
Section: Highlighting Exerkines In Cancer Cachexiamentioning
confidence: 99%